THE UROPOD-BEARING LYMPHOCYTE OF THE GUINEA PIG : EVIDENCE FOR THYMIC ORIGIN - Rosenstreich, David L. (The Rockefeller University Press, 1972)
In this study, the frequency of uropod formation and the type of lymphocyte bearing the uropod was investigated in various guinea pig lymphocyte populations. Without prior in vitro stimulation, almost 40% of peritoneal exudate lymphocytes (PELS) form uropods, while thymocytes and lymph node cells form far fewer. Subsequent stimulation in vitro with purified protein derivative demonstrated that there is an association between antigen reactivity and frequency of uropod formation in these populations. The ultrastructure of these uropods is identical to that described for human lymphocytes stimulated with phytohemagglutinin. In the populations studied, all the lymphocytes forming uropods lack easily detectable surface membrane immunoglobulin and are therefore most likely thymus-derived or T lymphocytes.